IMPROVING STUDENTS’ VOCABULARY MASTERY USING ENGLISH SONG - Harjanto, Wahyu; Handayani, Sri (English Education Department Slamet Riyadi University Surakarta, 2025)
English is a universal language and needs habituation, and they are not used to learn English. Lack of facilities, the lack of available facilities makes learning seem old-fashioned and boring. The data use to describe the situation during teaching learning process. In this case, the researcher needs to analyze quantitative and qualitative data. In quantitative data, the test consists of pre-test and post-test, for qualitative data the researcher use observation as a method of analyze the data. The implementation of English songs in teaching and learning vocabulary has a positive impact for students in increasing desire to learn the vocabulary, the ease of remembering vocabulary, ease in interpreting the message of a word, learning about grammar and to focus the attention of students. This also supported by the result of the research at the pre-test in the first cycle before giving a treatment teaching using an English song the mean score of the pre-test was 6.80. and after giving a treatment in 5 meetings in 2 cycles by giving 4 indicators of vocabulary mastery the mean of the score was 7,20 in the first posttest to 7,80 in the second posttest. Keywords: Vocabulary, Vocabulary Mastery, English song, Classroom Action Research